1996
DOI: 10.1016/0014-5793(96)00329-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the cytochrome P‐450IIC18 (CYP2C18) gene and a novel member of the CYP2C subfamily

Abstract: The CYP2CI8 gene was investigated in order to characterize its molecular basis in the CYP2C subfamily. A mutation of the CYP2C18 gene was identified at the 5'-flanking region of the gene, which could be detected by digestion with DdeI. The allele frequency of the mutant CYP2C18 gene was 21.4%. Genotypes of the polymorphic DdeI site of the CYP2C18 gene were found to be completely consistent with that of the polymorphic CYP2C19 gene (the ml mutant). The CYP2CI8 and CYP2CI9 genes were suggested to be linked and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…CYP2C8 also plays a direct role in the metabolism of some important therapeutic drugs, including paclitaxel, amodiaquine, troglitazone, amiodarone, verapamil, cerivastatin, and fluvastatin. 10 Although variant CYP2C18 alleles have been reported, 1112 CYP2C18 expression is not consistent with a major role in hepatic drug metabolism and specific CYP2C18-substrates have yet to be clearly identified. 3 Both common and rare CYP2C19 , CYP2C9 , and CYP2C8 variant alleles have been identified in different populations, which are catalogued by the Human Cytochrome P450 (CYP) Allele Nomenclature Committee.…”
Section: Introductionmentioning
confidence: 99%
“…CYP2C8 also plays a direct role in the metabolism of some important therapeutic drugs, including paclitaxel, amodiaquine, troglitazone, amiodarone, verapamil, cerivastatin, and fluvastatin. 10 Although variant CYP2C18 alleles have been reported, 1112 CYP2C18 expression is not consistent with a major role in hepatic drug metabolism and specific CYP2C18-substrates have yet to be clearly identified. 3 Both common and rare CYP2C19 , CYP2C9 , and CYP2C8 variant alleles have been identified in different populations, which are catalogued by the Human Cytochrome P450 (CYP) Allele Nomenclature Committee.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of these polymorphisms have not been examined clinically. Polymorphisms of CYP2C18 have also been described [14, 15], but CYP2C18 protein has not yet been found in detectable amounts in any tissues. Until this protein is shown to have some function in vivo , the polymorphisms in this enzyme are primarily of intellectual interest.…”
Section: Introductionmentioning
confidence: 99%
“…This anomaly yielded a truncated 67-amino-acid CYP2C18 lacking a haem-binding region. Tsuneoka et al (1996) discovered a single nucleotide change (T to C) at position À478 of the 5 Hanking region (CYP2C18m2). Mamiya et al (1998) recently reported that, in a Japanese population, genotypes of CYP2C18m1 and CYP2C18m2 were completely coincident with those of CYP2C19*3 and CYP2C19*2, respectively.…”
mentioning
confidence: 99%
“…CYP2C19*1 and the mutated alleles, CYP2C19*2 and CYP2C19*3, were identi®ed by PCR ampli®cation with speci®c primers and by the restriction fragment length polymorphism (RFLP) procedure described by de Morais et al (1994a, b). CYP2C18wt and the mutated alleles, CYP2C18m1 and CYP2C18m2, were identi®ed by PCR ampli®cation using speci®c primers and by the RFLP methods described by Komai et al (1996) and by Tsuneoka et al (1996), respectively.…”
mentioning
confidence: 99%